(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
This research aims to understand and to evaluate the ability of the rehabilitation programs to assist brother and sisters with their dabbled sibling involvement and interaction from the parents point of view. Theresearcher made a questionnaire for the purpose of this research, and distributes it on 35 families in Amman- Jordan. The results show that the rehabilitation programs for disabled children could be able to push the involvements of the disabled child in the family and to establish better connection with his/her siblings. The results show that the programs reduce introvert status of the child and increase interaction with his siblings. هذا البحث يهدف إلى التعرف على قدرة البرامج التاهيلية والعلاجية على دمج الطفل من ذوي الاحتياجات الخاصة في أسرته وبخاصة مع أخوته وأخواته, لما لذلك من أهمية كبرى في تطوره ونموه, وتأقلم الأخوة الطبيعيين مع الابن من ذوي الاحتياجات الخاصة. قام الباحث بتصميم استبانة خاصة لهذا البحث وتم توزيعها على 35 عائلة لديها أطفال طبيعيين وأطفال من ذوي الحاجات الخاصة, وتم جمع البيانات عن طريق زيارات إلى البيوت. أظهرت النتائج أن برامج التأهيل والعلاج أسهمت في دمج الطفل من ذوي الاحتياجات الخاصة مع أخوته , وأسهمت في خفض الانعزال والانطواء , وساهمت في دمج الطفل مع عائلته بشكل كلي , وغيرت تعامل الأبناء مع الطفل بشكل ايجابي بحسب أراء الآباء.